Experiencias y replanteamientos de la ordenación del territorio en Europa. Retos en relación con la calidad - Bielza de Ory, Vicente (Geographicalia, 2016)
It’s started from a revision of the experiences which were had in Western Europe countries until 1973 crisis, when the personalized territorial policies of the different states tended to give priority either the balanced development of regions or the phisical organization of the space, by using in most cases centralistic, stritc, developmental, little participating, and even imposible to carry out plans. With the solution of the economic crisis, crisis that pushed the planning in the european states into the background, the 1983 Europen Carte following the line of D. Stamp’s holistic view of classic applied geography sets out convergency of the two objectives of Territorial Planning . In the 90’s beginning, scientists -french case- will open a debate about the new prospective making clear the necessity of decentralized, sustainable, dermocratic participating, flexible, like permanent processes, negotiables and so on plans. Those notes saturated the new 1995 French law and the information emanated from the EU, which will end in the 1999 Territorial European Strategy where six great challenges are set out related to the balanced sustainable territorial development from a multi-centered cities system and the new country-town relationship